Lipoprotein metabolism during acute inhibition of lipoprotein lipase in the cynomolgus monkey. - Goldberg, I J (1988)
To clarify the role of lipoprotein lipase (LPL) in the catabolism of nascent and circulating very low density lipoproteins (VLDL) and in the conversion of VLDL to low density lipoproteins (LDL), studies were performed in which LPL activity was inhibited in the cynomolgus monkey by intravenous infusion of inhibitory polyclonal or monoclonal antibodies. Inhibition of LPL activity resulted in a three- to fivefold increase in plasma triglyceride levels within 3 h. Analytical ultracentrifugation and gradient gel electrophoresis demonstrated an increase predominantly in more buoyant, larger VLDL (Sf 400-60). LDL and high density lipoprotein (HDL) cholesterol levels fell during this same time period, whereas triglyceride in LDL and HDL increased. Kinetic studies, utilizing radiolabeled human VLDL, demonstrated that LPL inhibition resulted in a marked decrease in the catabolism of large (Sf 400-100) VLDL apolipoprotein B (apoB). The catabolism of more dense VLDL (Sf 60-20) was also inhibited, although to a lesser extent. However, there was a complete block in the conversion of tracer in both Sf 400-100 and 60-20 VLDL apoB into LDL during LPL inhibition. Similarly, endogenous labeling of VLDL using [3H]leucine demonstrated that in the absence of LPL, no radiolabeled apoB appeared in LDL. We conclude that although catabolism of dense VLDL continues in the absence of LPL, this enzyme is required for the generation of LDL.